TAXPAYER COMPLIANCE THROUGH KNOWLEDGE OF TAXATION AND E-COMMERCE TAX REGULATION POST COVID-19 - Maulana Margribi, Robi; Hernita, Nita; Kusumadewi, R. Neny (Indonesia Accounting Research Journal, 2024)
Covid-19 has had a real impact on business actors who use the digital world as a place to do business, namely e-commerce . There are many high-income companies, where the government issues regulations regarding e-commerce taxes , but it is not proportional to the amount of tax received by the government. This study aims to empirically prove the effect of tax knowledge and E-commerce tax regulations on taxpayer compliance in Majalengka Regency. This research is a quantitative research using primary data with data collection techniques using questionnaires that are measured using a Likert scale. The population of this research is individual taxpayers who do e-commerce business , totaling 78 people. The sampling technique in this study used purposive sampling with a total of 78 respondents. The data analysis technique used is multiple regression analysis technique with SPSS version 21. The research findings show that tax knowledge has no effect on taxpayer compliance at KP2KP Majalengka. E-commerce tax regulations have a positive and significant effect on taxpayer compliance. Limitations of research provide initial and descriptive analysis. Further analysis is needed to better identify causality and co-factors. Practical implications for research Knowledge of taxation and post-Covid-19 tax regulations is very sensitive to the needs of taxpayers. The originality of the research uses an original data set that produces new data that explains how the pandemic has affected the needs of taxpayers. It focuses on Majalengka Regency, West Java Province, an area that has been particularly hard hit by having a large number of taxpayer needs